Soft Target - Hunter, Stephen 1946- (New York : Simon & Schuster, 2011)
A follow-up to "Dead Zero" finds retired marine sergeant Ray Cruz confronting a band of terrorists who have taken over the Mall of America, where they begin to systematically execute more than one thousand hostages.
Keywords: Terrorism -- Fiction -- Prevention; Minnesota -- Fiction; Adventure fiction